View Single Post
mmajames
#4
Mar9-12, 06:59 PM
P: 12
First and Second Derivatives

f(x)=X2/(x2-16)
(X2-16)(2X)-(X2)(2X)/(X2-16)2
f'(x)=-32X2/(X-16)2
(X4-32X4+256)(-64X)-(-32X2)(4X3-64X)/(X4-32X2+256)2
-64x^5+2048X^3-16384X+128X5-2048X3
f''(x)=64X5-16384X/(X4-32X^2+256)2

f(x)=(1+x)/(1-X)
(1-X)(1)-(1+X)(-1)/(1-X)2
f'(x)=2-2X/(1-X)2
(-2X+1)(-2)-(2X-2)(2-2X)/(X2-2X+1)2
f''(x)=2X2+4X+2/(X2-2X+1)22

f(x)=X3(X-2)2
(X3)(2X-4)+(3X2)(X-2)2
2X4-4X3+3X4-12X3+12X2
f'(x)=5X4-16X3+12X2
5X^4-163+12X2
f''(x)=20X3-48X2+24X



And yes Three different functions